Konsep Gerakan Dakwah Hidayatullah dalam Buku Panduan Berislam - Hartati, Sri, Dr. Syamsul Hidayat, M.Ag, Dr. Muinudinillaah Basri, MA (2015)
Dakwah movement in an islamic mass organizations occupy an important position as an amar ma'ruf nahi munkar. The existence of a real concept agreed and then will determine the steps to achieve the vision. On this basis, this research focuses on the concept of Hidayatullah dakwah movement in the book Islamic Guidance. This book is the development of idea Abdullah Said and published by the Central Board of Hidayatullah. The formulation of this research are: 1) the concept of dakwah movement in Hidayatullah, 2) the reason for making berislam quide book to formulate the concept of dakwah movement, and 3) how the relevance towards Hidayatullah Islamic Thought. There are three objectivies of this research, namely: first to identify and describe concepts of Hidayatullah dakwah movement in the book Islamic Guidance. Second, find the urgency of preparing Handbook of Islamic Guidance. Third, explain the relevance of the concept of Dakwah by Hidayatullah Islamic Thought. This research is a library research with descriptive type. The primary source of this research is the Handbook of Islamic Guidance. The secondary sources used were book published by other Hidayatullah either written by teams and individuals that are relevant to research, document, and some of the result of previous research. To understand to content of the primary sources, this research uses content analysis method and then the results were analyzed with a historical approach to explain the concept of the dakwah movement and its relevance of Hidayatullah Islamic Thought. Based on the research results, it was found that the concept of Hidayatullah dakwah movement known as Sistematika Nuzulnya Wahyu (SNW) is reduced from the order of the first decline in five revelation. SNW is a genuine conception of Abdullah Said thought that decompiling classical literatures to imitate the sequence and stages of Prophet's dakwah trip called Prophetic manhaj. Then preserved and developed as manhaj of Hidayatullah movement. Handbook of Islamic guidance which consists of five packets is an integral and sequential circuit, which sistematics adjusted to the order nuzulnya five first revelation, become compulsory subject Training Marhalah and coaching aqidah dakwah cadres. So the bookkeeping of an idea and the idea into something that is important for fostering cadres remain systematic and consistent dakwah. So it can be concluded that Hidayatullah Islamic rationale is based on the inception of the natural view of Islam (Islamic Worldview) i.e. when the first revelation at the same time be the beginning of the trip propaganda Prophet.